Management of Lead Content for Growth of {001}‐Oriented Lead Magnesium Niobate‐Lead Titanate Thin Films. Issue 4 (2nd March 2016) - Keech, Ryan; Shetty, Smitha; Wang, Ke; Trolier‐McKinstry, Susan
Abstract : A scalable growth process for domain engineered {001}‐oriented lead magnesium niobate—lead titanate (PMN‐PT) thin films with Lotgering factors of 0.98–1.0, without an orienting perovskite seed layer, is presented. Deposition of a 2–3‐nm‐thick PbO buffer layer on {111} Pt thin film bottom electrodes, prior to chemical solution deposition of PMN‐PT reduces the driving force for Pb diffusion from the PMN‐PT to the bottom electrode, and facilitates nucleation of {001}‐oriented perovskite grains. Energy dispersive spectroscopy demonstrated that up to 10% of the Pb from a PMN‐PT precursor solution may diffuse into the bottom electrode. PMN‐PT grains with a mixed {101}/{111} orientation in a matrix of Pb‐deficient pyrochlore phase were then promoted near the interface. When this is prevented, phase‐pure films with {001} orientation can be achieved.